(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper reviews literature from 2011 to 2013 on how Latent attributes like gender, political leaning etc. can be inferred from a person’s twitter and neighborhood data. Prediction of demographic data can bring value to businesses, can prove instrumental in legal investigation. Moreover, political leanings and ethnicity can be inferred from the wide variety of user data available on-line. The motive of this review is to understand how large datasets can be made from available twitter data. The tweeting and re tweeting behavior of a user can be user to infer attributes like, gender, age etc. We’ll also try to understand the applications of Machine learning and Artificial Intelligence in this task and how it can be improved for future prospects. We explore in this text how this field can be expanded in future and possible avenues for future research.